Cardiac Overexpression of XIN Prevents Dilated Cardiomyopathy Caused by TNNT2 ΔK210 Mutation - Li, Bin; Guo, Yifan; Zhan, Yongkun; Zhou, Xinyan; Li, Yongbo; Zhao, Chao; Sun, Ning; Xu, Chen; Liang, Qianqian (Frontiers in Cell and Developmental Biology, 2021)
TNNT2 mutation is associated with a range of cardiac diseases, including dilated cardiomyopathy (DCM). However, the mechanisms underlying the development of DCM and heart failure remain incompletely understood. In the present study, we found the expression of cardiac XIN protein was reduced in TNNT2-ΔK210 hESCs-derived cardiomyocytes and mouse heart tissues. We further investigated whether XIN protects against TNNT2 mutation-induced DCM. Overexpression of the repeat-containing isoform XINB decreased the percentage of myofilaments disorganization and increased cell contractility of TNNT2-ΔK210 cardiomyocytes. Moreover, overexpression of XINB by heart-specific delivery via AAV9 ameliorates DCM remodeling caused by TNNT2-ΔK210 mutation in mice, revealed by partially reversed cardiac dilation, systolic dysfunction and heart fibrosis. These results suggest that deficiency of XIN may play a critical role in the development of DCM. Consequently, our findings may provide a new mechanistic insight and represent a therapeutic target for the treatment of idiopathic DCM.